Maslow's and Freud's Theories Reflected in Andrew Laeddis' Character - Friskila Yesika Novelia Hutagaol; Agnes Widyaningrum (LPPM Universitas Bumigora Mataram, 2023)
This research explores the portrayal of schizophrenia symptoms in the character Andrew Laeddis from the movie